Community of Lombok’s Tradition Effects the Nutrient Intake Behavior in Pregnant Woman - Ni Ketut Alit Armini; Retnayu Pradanie; Putu Widhi Sudariani (Universitas Airlangga, 2009)
Introduction: Tradition about nutrient intake in pregnant women had being spreaded in the society and it can influence the behaviour of pregnant women in the fulfilment of nutrient intake in pregnancy. Lombok area is still following the nutrient intake tradition. The objective of the study was examine the relation between tradition of Lombok community with the nutrient intake behaviour in pregnant woman in the working area of Public Health Center Perampuan, Labuapi District, West Lombok Regency. Method: This study used cross sectional design. The population was all pregnant women that came to the Puskesmas Public Health Center Perampuan, Labuapi District, West Lombok Regency each month. Sample formulation used purposive sampling. Total sample were 45 respondents that were taken according to inclusion criteria. Independent variable was tradition of Lombok community and dependent variable was the nutrient intake behaviour in pregnant woman. Data were collected using questionnaire, interview, respondent observation and dietary recall 24 hours. Data were analyzed with correlation Spearman Rho, with significance value α≤0.05. Result: The result showed that there were corelation between tradition of Lombok community with the knowledge (p=0.002), attitude (p=0.001). the action of nutrient intake in pregnant woman of the fulfilment nutrient intake in pregnancy. Discussion: Further studies should do the research to change the negativity behaviour causes by tradition of community, specially for nutrient intake in pregnancy, such as continuously health education.